1987
DOI: 10.1007/bf01646053
|View full text |Cite
|
Sign up to set email alerts
|

Single and multiple dose pharmacokinetics of intravenous cefpirome (HR 810), a novel cephalosporin derivative

Abstract: After intravenous injection of single doses of 1.0 g of cefpirome (HR 810) and multiple doses of 1.0 g b.i.d. for five days to the same ten healthy male volunteers in an open design, concentrations of unchanged drug were estimated at various times in serum and urine, over 24 h and 48 h, respectively. Cefpirome concentrations were determined using both high pressure liquid chromatography (HPLC) and a microbiological assay. The measurements obtained were compared by linear distribution independent regression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous investigators [1013] have also involved various microbiological assay methods, including both microdilution and agar dilution, to quantitate cefpirome. Two studies [13, 14] reported the pharmacokinetics of cefpirome in adults after quantitation of the compound in serum by using high-performance liquid chromatography (HPLC) assay for which specific details were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators [1013] have also involved various microbiological assay methods, including both microdilution and agar dilution, to quantitate cefpirome. Two studies [13, 14] reported the pharmacokinetics of cefpirome in adults after quantitation of the compound in serum by using high-performance liquid chromatography (HPLC) assay for which specific details were not provided.…”
Section: Introductionmentioning
confidence: 99%